(untitled) (Canadian Medical Education Journal, 2018)
This paper describes the use of Kane’s validity framework to redevelop a workplace-based assessment program for practicing physicians administered by the College of Physicians and Surgeons of Ontario. The developmental process is presented according to the four inferences in Kane’s model. Scoring was addressed through the creation of specialty-specific assessment criteria and global, narrative-focused reports. Generalization was addressed through standardized sampling protocols and assessor training and consensus-building. Extrapolation was addressed through the use of real-world performance data and an external review of the scoring tools by practicing physicians. Implications were theoretically supported through adherence to formative assessment principles and will be assessed through an evaluation accompanying the implementation of the redeveloped program. Kane’s framework was valuable for guiding the redevelopment process and for systematically collecting validity evidence throughout to support the use of the assessment for its intended purpose. As the use of workplace-based assessment programs for physicians continues to increase, practical examples are needed of how to develop and evaluate these programs using established frameworks. The dissemination of comprehensive validity arguments is vital for sharing knowledge about the development and evaluation of WBA programs and for understanding the effects of these assessments on physician practice improvement.